Effect of Dual‐Task Training on the Number of EEG Bands in Stroke Patients. - Asadi, Borhan; Khodabakhshi, Zahra; Naimi, Sedigheh Sadat; Herrero, Pablo; Ansari, Noureddin Nakhostin; Lapuente‐Hernandez, Diego (Physiotherapy Research International, 2025)
Background/Objective: Dual‐task training (DTT) positively impacts stroke recovery, but its effects on electroencephalography (EEG) using Fourier series analysis are under‐researched. This study aimed to evaluate the effects of DTT on EEG in stroke patients by analyzing different EEG bands with fast Fourier transform (FFT). Methods: Five participants with unilateral ischemic stroke completed 12 sessions of 15‐min DTT, three times a week for 4 weeks. EEG data were recorded before and after the intervention, and FFT analysis was conducted. Assessments of upper limb function, elbow flexor muscle tone, and daily living activities were also performed. Results: FFT analysis showed a reduction in delta, theta, alpha, and beta bands post‐DTT, while their correlation between measurement times remained consistent. These changes were somewhat reflected in the participants' improved clinical outcomes. Conclusion: The results suggest that DTT positively affects EEG band frequencies, with a consistent correlation between pre‐ and post‐intervention measurements. This indicates that FFT analysis could be a useful tool for assessing DTT's impact on stroke recovery.